Evaluation of Publication Rate of Forensic Medicine Specialty Theses in Turkey - Derya Çağlayan; Cemil Çelik; Ahsen Kaya; Ekin Özgür Aktaş (Adli Tıp Bülteni, 2020)
Objective: The aim of this study is to investigate the publication rate of Forensic Medicine specialty theses in national and international journals.